Too Purply! - Reidy, Jean; Illustrated by Leloup, Genevieve (London Bloomsbury, 2010)
It's time to get dressed and a determined child knows exactly which clothes she wants to where and which she doesn't. Suggested level: junior.
Include Color Illustrations
Keywords: Clothing and dress -- Fiction -- Stories in rhyme